Direct stimulation of the autonomic nervous system modulates activity of the brain at rest and when engaged in a cognitive task. Issue 7 (27th February 2012) - Basile, Barbara; Bassi, Andrea; Calcagnini, Giovanni; Strano, Stefano; Caltagirone, Carlo; Macaluso, Emiliano; Cortelli, Pietro; Bozzali, Marco
Abstract The effect of autonomic perturbation (AP) on the central nervous system functioning is still largely unknown. Using an automated neck suction device to stimulate the carotid mechanoreceptors in the carotid sinus (parasympathetic pathway), operated synchronously with functional magnetic resonance imaging (fMRI) acquisition, we investigated the effects of AP on the activity of the brain at rest and when engaged in a visuo‐spatial attention task. ECG was always recorded to index changes in autonomic function. At rest, AP induced increased activation in the insula and in the amygdala, which have been previously associated with the autonomic control and emotion processing, as well as in the caudate nucleus and in the medial temporal cortex, both implicated in cognitive functions. Despite a preserved performance during visuo‐spatial attention task, AP induced increased reaction times and a positive modulation on the activation of the right posterior parietal cortex, the occipital cortex, the periaquiductal gray, and nuclei of the brainstem. We speculate that this modulation of brain activity represents, at different anatomical levels, a compensation mechanism to maintain cognitive efficiency under parasympathetic stimulation, which is traditionally considered as the system for energy regain and storage. In conclusion, this study provides the first evidence of a dynamic interaction between AP and higher level functions in humans. Hum Brain Mapp, 2013. © 2012 Wiley Periodicals, Inc.